The incidence of local government allocations in Tanzania - Boex, Jameson (2003)
Since 1999, Tanzania has been actively pursuing reforms of the way in which the central government finances local government activities. This article looks at the potential problems with the mechanism that the central government currently uses to distribute budget resources among the 114 local government authorities and sets out to reveal the incidence of central government allocations to local authorities in Tanzania. Two strands of economics literature - the public choice literature and the political economy literature - consider the distribution of central government resources across local governments. Using regression analysis, this study specifies an incidence model that reveals the determinants of variations in local government allocations in Tanzania. The empirical analysis only finds weak evidence supporting the presumed pro-poor allocation of some local government resources by the central government in Tanzania. Instead, the study finds more convincing support for substantial pro-wealthy and pro-urban tendencies in the way in which central government officials divide public resources across local government units. - Reproduced.
Keywords: Local government - Tanzania; Local government